Reactions of platinum complexes with 4,7-phenanthroline: crystal structures of mono- and binuclear platinum(II) complexes containing 4,7-phenanthroline - Momeni, Badri Z.; Fathi, Nastaran; Shafiei, Maliheh; Ghasemi, Fahimeh; Rominger, Frank (Journal of coordination chemistry, 2016)
The reaction of a mixture of cis and trans-[PtCl2(SMe2)2] with 4,7-phen (4,7-phen = 4,7-phenanthroline) in a molar ratio of 1 : 1 or 2 : 1 resulted in the formation of mono and binuclear complexes trans-[PtCl2(SMe2)(4,7-phen)] (1) and trans-[Pt2Cl4(SMe2)2(μ-4,7-phen)] (2), respectively. The products have been fully characterized by elemental analysis, 1H, 13C1H, HHCOSY, HSQC, HMBC, and DEPT-135 NMR spectroscopy. The crystal structure of 1 reveals that platinum has a slightly distorted square planar geometry. Both chlorides are trans with a deviation from linearity 177.66(3)°, while the N-Pt-S angle is 175.53(6)°. Similarly, the reaction of a mixture of cis and trans-[PtBr2(SMe2)2] with 4,7-phen in a 1 : 1 or 2 : 1 mole ratio afforded the mono or binuclear complexes trans-[PtBr2(SMe2)(4,7-phen)] (3) and trans-[Pt2Br4(SMe2)2(μ-4,7-phen)] (4), respectively. The crystal structure of trans-[Pt2Br4(SMe2)2(μ-4,7-phen)].C6H6 reveals that 4,7-phen bridges between two platinum centers in a slightly distorted square planar arrangement of the platinum. In this structure, both bromides are trans, while the PtBr2(SMe2) moieties are syn to each other. NMR data of mono and binuclear complexes of platinum 1-4 show that the binuclear complexes exist in solution as a minor product, while the mononuclear complexes are major products.
Gesehen am 08.09.2020